# Solve the followi

The parts of this question are solved below:

(a) Here,

We have to find the value of p

Thus,

10p = 100

Now,

Dividing both sides by 10, we get: = Therefore,

p = 10

(b) Here,

We have to find the value of p

Thus,

10p + 10 = 100

10p = 100 – 10

10p = 90

Now,

Dividing both sides by 10, we get: = Therefore,

p = 9

(c) Here,

We have to find the value of p

Thus, = 54

Now,

Multiplying both sides by 4, we get: = 5 × 4

Therefore,

p = 20

(d) Here,

We have to find the value of p

Thus, = 5

Now,

Multiplying both sides by -3, we get: = 5 × -3

Therefore,

p = - 15

(e) Here,

We have to find the value of p

Thus, = 6

Now,

Multiplying both sides by 4, we get: = 6 × 4 = Therefore,

p = 8

(f) Here,

We have to find the value of s

Thus,

3s = -9

Now,

Dividing both sides by 3, we get: = Therefore,

s = -3

(g) Here,

We have to find the value of s

Thus,

3s + 12 = 0

= 3s + 12 – 12 = 0 – 12

3s = -12

Now,

Dividing both sides by 3, we get: = Therefore,

s = -4

(h) Here,

We have to find the value of s

Thus,

3s = 0

Now,

Dividing both sides by 3, we get: = Therefore,

s = 0

(i) Here,

We have to find the value of q

Thus,

2q = 6

Now,

Dividing both sides by 2, we get: = Therefore,

q = 3

(j) Here,

We have to find the value of q

Thus,

2q – 6 + 6 = 0 + 6

2q = 6

Now,

Dividing both sides by 2, we get: = Therefore,

q = 3

(k) Here,

We have to find the value of q

Thus,

2q + 6 - 6 = 0 - 6

2q = - 6

Now,

Dividing both sides by 2, we get: = Therefore,

q = - 3

(l) Here,

We have to find the value of q

Thus,

2q + 6 - 6 = 12 - 6

2q = 6

Now,

Dividing both sides by 2, we get: = Therefore,

q = 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
RELATED QUESTIONS :

Solve the followiNCERT Mathematics

<span lang="EN-USNCERT Mathematics

x exceeds 3 by 7,NCERT - Exemplar Mathematics

If k + 7 = 16, thNCERT - Exemplar Mathematics

If <span lang="ENNCERT - Exemplar Mathematics

The equation haviNCERT - Exemplar Mathematics

If 43m = 0.086, tNCERT - Exemplar Mathematics

If 7x + 4 = 25, tNCERT - Exemplar Mathematics

Shifting one termNCERT - Exemplar Mathematics

Which of the follNCERT - Exemplar Mathematics